NetScope traffic engineering for IP networks. - Feldmann, A. (IEEE Network : the magazine of global information exchange)
Managing large IP networks requires an understanding of the current traffic flows, routing policies, and network configuration. However, the state of the art for managing IP networks involves manual configuration of each IP router, and traffic engineering based on limited measurements. The networking industry is sorely lacking in software systems that a large Internet service provider can use to support traffic measurement and network modeling, the underpinnings of effective traffic engineering. This article describes the AT&T Labs NetScope, a unified set of software tools for managing the performance of IP backbone networks. The key idea behind NetScope is to generate global views of the network on the basis of configuration and usage data associated with the individual network elements. Having created an appropriate global view, we are able to infer and visualize the networkwide implications of local changes in traffic, configuration, and control. Using NetScope, a network provider can experiment with changes in network configuration in a simulated environment rather than the operational network. In addition, the tool provides a sound framework for additional modules for network optimization and performance debugging. We demonstrate the capabilities of the tool through an example traffic engineering exercise of locating a heavily loaded link, identifying which traffic demands flow on the link, and changing the configuration of intradomain routing to reduce the congestion